Perkembangan Anak pada Masa Sekolah Dasar - Sinta Zakiyah; Nurul Hidayah Hasibuan; Aufa Yasifa; Suhaila Putri Siregar; Olivia Wahyu Ningsih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Children's development during elementary school includes various aspects such as cognitive, social, emotional, physical and language. Every child develops in various unique ways, but there are several general developments that can be identified in elementary school children, namely children aged 6 to 12 years. As for physical development, at this age children experience rapid body growth, fine and gross motor skills continue to develop. As for the cognitive development of children during this period, they acquire higher cognitive abilities. In social development, children at this time understand and are involved in more complex social interactions. During this period of emotional development, children learn to manage emotions better, identify and express feelings more accurately. The aim of this research was to find out specifically the development of children during elementary school. In this research, the author uses a type of research in the form of library research. From this research, the researcher concluded that aspects of a child's development can be influenced by the surrounding environment. Therefore, teachers and parents should have knowledge in efforts to maximize aspects of a child's development because, if every aspect can develop well, then the child is able to carry out tasks. the task of development is also good.